Jews, Essayists, and Other Genreless People: Brenner and His Literary Times - Berdichevsky, Dina (MiKAN, 2020)
This article returns once again to Y.H. Brenner's famous 1911 essay, "The Eretz-Israeli Genre and its Accountrements". This essay has long been canonized as representative of renner's truthfulness, and as the boldest manifestation of his contempt for deception, decorative beauty, and idylls. Within the chronicles of Hebrew literary history, "The Eretz-Israeli Genre and its Accoutre ments" beca,r most associated with Brenner's realist norms and his emphasis on literature's political and social obligation. Exploring the publication of Brenner's essay within the context of the wider cultural, political and literary developments of the early 20th century, this article suggests that rather then heralding Eretz-Israeli realism, Brenner's essay features the swan song of Jewish essayistic modernism. Facing the nationalization of literary activity in Palestine/Eretz-Israel, Brenner seeks to preseve the essaytic modernist style - with all its epistemic rootlessness and poetic transivity - which was formed in Europe during the nascent years of the 20th century. However, this effort was doomed to fail, in its concluding section, the article shows how dramatic and rapid was the aesthetic political upheaval that took place in the afteremath of World War I, which pushed aside all the literary values Brenner heralded in his essayistic manifesto. Furthermore, it demonstrates how vital and central was role that Brenner himself played in this literary upheaval marked by national realism.